In vitro and in vivo studies on the neuropeptide thyrotropin-releasing hormone (TRH) - Cullen, Aoife (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2009)
Thyrotropin-releasing hornnone (pyroglutamyl-histidyl-prolineamide; TRH), a tripeptide, a hypothalamic-pituitary-thyroid axis hormone, has neuromodulatory properties and is found in the brain in locations where it has no pituitary or thyroid functions. It is released from nerve terminals in response to depolarisation and has both stimulatory and inhibitory effects on post-synaptic neurones. TRH co-localises with several neurotransmitters including acetylcholine, serotonin and glutamate. The interaction that TRH has with these neurotransmitters and the dual role it plays in either stimulation or inhibition of the neurones it acts on suggest TRH may be a key homeostatic modulator. Furthermore, it may protect against pathological changes or insults to the central nervous system (CNS).
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin